2021
DOI: 10.3389/fonc.2021.711736
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Prognostic Model Based on Autophagy-Related Long Non-Coding RNAs for Clear Cell Renal Cell Carcinoma

Abstract: BackgroundRenal cell carcinoma (RCC) is one of the most common malignant tumors of the urinary system, of which the clear cell renal cell carcinoma (ccRCC) accounts for the most subtypes. The increasing discoveries of abundant autophagy-related long non-coding RNAs (ARLNRs) lead to a resurgent interest in evaluating their potential on prognosis prediction. Based on a large number of ccRCC gene samples from TCGA and clinics, ARLNRs analysis will provide a novel perspective into this field.MethodsWe calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…AC011462.4 has been reported to play an important oncogenic role in tumors. Li et al (2021) revealed that the high expression level of AC011462.4 was associated with longer OS. The expression level of AC011462.4 increased with the increase of risk score in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…AC011462.4 has been reported to play an important oncogenic role in tumors. Li et al (2021) revealed that the high expression level of AC011462.4 was associated with longer OS. The expression level of AC011462.4 increased with the increase of risk score in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…And MIR200CHG was found to be a protective indicator for bladder cancer patients ( 27 ). AC008735.2 was significantly associated with targeted therapy and prognosis in patients with clear cell renal cell carcinoma ( 28 ). KRT7-AS played an important role in cancer regulation and was superior to other clinicopathological features in predicting survival ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a risk score model, AC010894.3 was included in a four-lncRNA signature that accurately predicted the OS of OC patients, and its increased expression was associated with better survival [ 62 ]. Three other lncRNAs from our gene list, AC244502.1 , AP002807.1 , and AP002518.2 , were integrated into prognostic signatures for breast cancer, clear cell renal cell carcinoma, and Wilms tumor, respectively [ 65 , 66 , 67 ]. The lncRNA SNHG12 was selected as a candidate due to its inverse correlation between high expression levels and DNA hypomethylation in carboplatin-resistant OC cell lines.…”
Section: Discussionmentioning
confidence: 99%